The Impact of Technology-Enhanced EFL Reading Classes on Learners’ Performances and Participations - Nishat Tasneem (University of Darussalam Gontor, 2022)
The paper analyzes learners’ performances, attitudes, preferences, expectations, and judgments to estimate the contemporary impact of Technological-enhanced Language Learning (TELL) in the higher secondary EFL reading context of Bangladesh. The research is conducted among 3 higher secondary level schools in Dhaka City. These schools use both traditional modules and technology-enhanced modules to teach the students. The research utilizes a mixed method approach to address the current gap in studies in regards to a lack of research that emphasizes evaluating the impact of technology-enhanced classes in the higher secondary level EFL context in a developing country like Bangladesh. Findings reflect the implication of technology in producing Krashen’s (1981) low affective filter in the pedagogical reading environment by creating a conducive and comprehensible reading sphere. This also helps in promoting learners’ reading interests and motivation. The findings also highlight the fact that technological interventions in reading classes help alleviate their performances and participation in EFL classes. However, the findings manifest a limitation in using such technological modes in developing learners’ academic reading skills in the developing country context of Bangladesh. The study concludes by drawing on some learner-oriented suggestions to improve technology-enhanced EFL reading classes in the particular context.